Prevalence of Cyberchondria Among Students in Selected Colleges - A Cross Sectional Study - Geetha, Geetha; Shaji J C, Helen; Arivukarasi, Arivukarasi; Gangeshwari K, T; S, Dhivya (Journal of Neonatal Surgery, 2025)
The internet is a source for providing valuable health regarding information.However when it is used for diagnostic purpose ,it may lead to occurrence and prevalence of cybercondria among the college students.Cyberchondria develops due to expose to the vast and easily accessible online health related information that causes unwanted health worries.Individuals with questions about their health often turn to the internet for information about their symptoms but the degree to which health anxiety is related online checking remains unclear .This one of the concerning topic has a large number of students search for health information in online.A cross – sectional study was conducted among college students in kattankulathur . two hundred and sixty four students were selected and data were collected using a semi structured questionnaire This study involved 46.21% of male and 48.09% of female and 5.30% of the students were not interested to say about their online health search information .The majority of college students in the sample (49.07%) are severely affected by cyberchondria, suggesting that many may experience anxiety or stress related to online health information.About 26% of students are not affected, while 21.1% are moderately affected.This suggests that cyberchondria is a significant issue among college students, with nearly 70% showing some level of concern, either moderate or severe Excessive searching for health information online has the potential to thread among the people and it may lead to an increase in cyberchondria . we can overcome this problem by creating awareness among the general public regarding proper usage of web search engine.